BATALNYA PUTUSAN BADAN ARBITRASE NASIONAL INDONESIA AKIBAT KETIDAKNETRALAN ARBITER - Sinaga, Devi Sarjani Lestari; Christine Susanti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Arbitration awards have a final and binding effect for the parties involved. However, under certain conditions, these awards can lose their enforceability due to formal defects in the decision. The East Jakarta District Court Decision Number 524/Pdt.Sus-Arb-2023/PN Jkt.Tim annulled the BANI Arbitration Award Number 45055/VII/ARB-BANI/2022 because one of the arbitrators was allegedly concealing the existence of a conflict of interest between the arbitrator and the legal counsel of one of the parties, which could affect the arbitrator’s neutrality in examining and adjudicating the case at BANI. This study is a normative legal research using a statutory and case approach. The results show that legal efforts made by PT HK Realtindo as the aggrieved party included filing a petition to annul the arbitration award in court based on Article 70 in conjunction with Article 72 paragraph (1) of the Arbitration Law. The petition to annul the arbitration award was granted through a court decision with the key legal consideration being that the arbitration award was obtained through deceit conducted by arbitrator Jelly Nasseri together with legal counsel Lena and others. Meanwhile, BANI’s response to the annulment petition was to assert that the arbitration proceedings at BANI applied the 2022 BANI Rules and Procedures as the applicable and binding procedural law for the parties, thus overriding Articles 70 through 72 of the Arbitration Law based on the legal principle of lex specialis derogate legi generali. Ultimately, the East Jakarta District Court annulled the BANI arbitration award, and BANI pursued legal remedies by filing a cassation petition to the Supreme Court based on Article 72 paragraph (4) of the Arbitration Law. Subsequently, the Supreme Court, through Decision Number 665 B/Pdt.Sus-Arbt/2024, affirmed the District Court’s decision.